Study protocol for the ACT response pilot intervention: development, implementation and evaluation of a systems-based Agitation Code Team (ACT) in the emergency department. Issue 6 (30th June 2020) - Wong, Ambrose H; Ray, Jessica M; Auerbach, Marc A; Venkatesh, Arjun K; McVaney, Caitlin; Burness, Danielle; Chmura, Christopher; Saxa, Thomas; Sevilla, Mark; Flood, Colin T; Patel, Amitkumar; Whitfill, Travis; et al.
Abstract : Introduction: Emergency department (ED) visits for behavioural conditions are rising, with 1.7 million associated episodes of patient agitation occurring annually in acute care settings. When de-escalation techniques fail during agitation management, patients are subject to use of physical restraints and sedatives, which are associated with up to 37% risk of hypotension, apnoea and physical injuries. At the same time, ED staff report workplace violence due to physical assaults during agitation events. We recently developed a theoretical framework to characterise ED agitation, which identified teamwork as a critical component to reduce harm. Currently, no structured team response protocol for ED agitation addressing both patient and staff safety exists. Methods and analysis: Our proposed study aims to develop and implement the agitation code team (ACT) response intervention, which will consist of a standardised, structured process with defined health worker roles/responsibilities, work processes and clinical protocols. First, we will develop the ACT response intervention in a two-step design loop; conceptual design will engage users in the creation of the prototype, and iterative refinement will occur through in situ simulated agitated patient encounters in the ED to assess and improve the design. Next, we will pilot the intervention in the clinical environment and use a controlled interrupted time series design to evaluate its effect on our primary outcome of patient restraint use. The intervention will be considered efficacious if we effectively lower the rate of restraint use over a 6-month period. Ethics and dissemination: Ethical approval by the Yale University Human Investigation Committee was obtained in 2019 (HIC #2000025113). Results will be disseminated through peer-reviewed publications and presentations at scientific meetings for each phase of the study. If this pilot is successful, we plan to formally integrate the ACT response intervention into clinical workflows at all EDs within our entire health system.